Menstrual cycle characteristics and associated physical problems among school going adolescent girls - Iyer, Pooja; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Onset of menstruation is the most marked physical change in an adolescent girl. Besides secondary sexual characters, other physical changes such as weight gain, acne etc. may trouble young girls. This study was carried out to study the characteristics of menstrual cycles and associated physical problems among the school going adolescent girls Methods: A predesigned survey questionnaire was administered to students of classes 6 to 12 prior to a health education talk at two urban schools in Bhopal. Results: Of 414 students, 413 responded to the questionnaire. The mean age of the girls was 14.4 years [range: 10-18; SD: 2]. Of these, 277 girls reported their age at menarche, the mean age being 12.7 years [range: 11.2-13; SD: 1.52] and a majority (58%) of them had regular menstrual pattern. A good proportion of then suffered from mild dysmenorrhoea (46%); nearly 18% reported severe dysmenorrhoea and 6% girls reported absence of dysmenorrhea. Only 16% of adolescent girls had consulted a doctor for symptoms related to menstrual cycle the rest took it as a natural course of events during menstruation. Among other physical changes besides secondary sexual characters, 32% suffered from acne, 24% reported weight gain and 21% had excessive hair growth. Conclusions: A good proportion of school going adolescent girls experience menstrual pattern deviation from normal and all so other problems such as acne, weight gain and excessive body hair. However, only a minority of them approach doctors for alleviation of these problems. Some of these problems may easily be addressed during the adolescent school health programs if held regularly.